2017
DOI: 10.1371/journal.pone.0182321
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of medically attended respiratory syncytial virus in older adults in the United States: A systematic review

Abstract: ObjectiveThis review was undertaken to assess the historical evidence of the disease incidence and burden of laboratory-confirmed respiratory syncytial virus (RSV) in medically attended older adults.DesignA qualitative systematic literature review was performed; no statistical synthesis of the data was planned, in anticipation of expected heterogeneity across studies in this population.MethodsA literature search of PubMed, Embase, and the Cochrane Library was conducted for studies of medically attended RSV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 50 publications
8
75
0
1
Order By: Relevance
“…In patients with other respiratory diseases, the prevalence of these viruses partially mirrored our findings. RSV was reportedly found in 12% of elderly patients with acute respiratory illnesses [13] and in 30.8% in Mexicans with acute upper respiratory tract infection [12], EnV was isolated from 37.0% of young infants with sepsis-like illnesses [14], and BoV was detected in 9.9% of nasopharyngeal aspirates from hospitalized children in Spain [15]. However, the prevalence of MpV was higher (10.6%) in Mexicans with acute upper respiratory tract infection [12], and the prevalence of AdV was also higher (15.0%) among hospitalized children in Spain [15] than that in our pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with other respiratory diseases, the prevalence of these viruses partially mirrored our findings. RSV was reportedly found in 12% of elderly patients with acute respiratory illnesses [13] and in 30.8% in Mexicans with acute upper respiratory tract infection [12], EnV was isolated from 37.0% of young infants with sepsis-like illnesses [14], and BoV was detected in 9.9% of nasopharyngeal aspirates from hospitalized children in Spain [15]. However, the prevalence of MpV was higher (10.6%) in Mexicans with acute upper respiratory tract infection [12], and the prevalence of AdV was also higher (15.0%) among hospitalized children in Spain [15] than that in our pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that RSV is the most common cause of hospitalization among children under 2 years of age and is associated with significant morbidity and mortality (Borchers et al, 2013;Nair et al, 2010;Shi et al, 2017). In elderly and immunocompromised adults or patients with preexisting diseases, the morbidity and mortality rates have been shown to be significantly higher in RSV-infected patients (Colosia et al, 2017). Therefore, RSV-related respiratory tract infection is a major public health issue worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestations after RSV infection range from a mild upper respiratory tract infection to severe life-threatening lower respiratory tract involvement such as bronchiolitis, pneumonia, and croup, together with some common symptoms including fever, rhinorrhea, cough, and wheezing (Borchers et al, 2013), which are not readily distinguished from those of other common respiratory virus infections. Although efforts to develop an RSV vaccine for all age groups began in the 1960s, no safe and effective vaccine is yet available, and antiviral treatment for RSV infection is currently also very limited, with treatments usually being supportive and symptomatic (Colosia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Though overshadowed by its preeminent importance among pediatric populations for several decades since its recognition as a human pathogen (Walsh and Falsey 2012), RSV has become an increasingly documented cause of illness in adults. In fact, several studies exploring and reporting the burden and clinical impact of RSV among adult populations across various geographical regions, in both outpatient and inpatient settings, have been published in the last two decades (Falsey et al, 2005;Lee et al, 2013;Volling et al, 2014;Mullooly et al, 2007;Thompson et al, 2003), including in recent years (Colosia et al, 2017;Ambrosch et al, 2018;Belongia et al, 2018;Kestler et al, 2018;Ackerson et al, 2019). RSV infections have been shown to be more severe among immunocompromised adults, those with cardiopulmonary conditions, and the elderly (Volling et al, 2014;Colosia et al, 2017;Belongia et al, 2018;Chatzis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies exploring and reporting the burden and clinical impact of RSV among adult populations across various geographical regions, in both outpatient and inpatient settings, have been published in the last two decades (Falsey et al, 2005;Lee et al, 2013;Volling et al, 2014;Mullooly et al, 2007;Thompson et al, 2003), including in recent years (Colosia et al, 2017;Ambrosch et al, 2018;Belongia et al, 2018;Kestler et al, 2018;Ackerson et al, 2019). RSV infections have been shown to be more severe among immunocompromised adults, those with cardiopulmonary conditions, and the elderly (Volling et al, 2014;Colosia et al, 2017;Belongia et al, 2018;Chatzis et al, 2018). Notably, various studies have suggested that the disease burden associated with RSV infections in the adult population is higher than that resulting from influenza virus infections, including in older adults (Kwon et al, 2017;Ambrosch et al, 2018;Kestler et al, 2018;Ackerson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%